ANALYSIS OF CHANGES OF BODY COMPOSITION WOMAN UNDER THE INFLUENCE OF AGE - Nebojša Čokorilo; Milena Mikalački; Stanislav Škrkar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: In modern civilization, there was a marked decrease in physical activity of people. It is well known that the use of dosed and regular physical activity act preventively to prevent the risk of diseases of modern civilization (Medved, 1980; Mišigoj Durakovic et al., 1999, Oman and Oman, 2003). The aim of the research is to analyze the changes of body composition of women affected by age. Methods: In a sample of 99 women, aged 20 to 49 years, the city of Novi Sad, undertook an assessment of body composition. The patients were divided into three subsamples with respect to age, for each decade separately. Distribution of respondents by age categories was made on the basis of some previous studies (NASIS and Geldas 2003, Flagg et al., 2005; Hayward, 2006). Univariate (ANOVA) and multivariate (MANOVA) analysis of variance fortified that there are statistically significant differences between all age groups, both in the common system variables and in most individual . For further determine the difference in the individual system variables was made t - test which confirms the findings of univariate analysis of variance. Results: Were found statistically significant differences between the analyzed groups. For most indicators of body composition are present in high and statistically significant differences. Discussion: Under the body composition we understand composition of the human body, represented by the size and grouping of existing measurable segments that constitute (Ugarković, 2001). According to some authors lean body mass is muscle, skeleton and internal organs, and body fat mass seems so. "important" and "unimportant" fat (Mišigoj Durakovic, 2006). References Bjorkelund, C., Lissner, L., Andresson, S., Lapidus, L., Bengtsson, C. (1996). Reproductive history in relation to relative weight and fat distribution. U International Journal of Obesity, 20, 213 - 219. Čokorilo, N., Mikalački, M., Korovljev, D. Cvetkovic, M. and Škrkar, S., (2012). Analysis of changes in body composition in women of different ages. Facta Universitatis - series: Physical Education and Sport, 10 (4), 347-353. Fleg, J. L., Morrell, C. H., Bos, A. G., Brant, L. J., Talbot, L. A., Wright, J. G., Lakatta, E.G. (2005). Accelerated longitudinal decline of aerobic capacity in healthy older adults. Circulation, 112, 674-682. Kohrt, W., M, Malley, M. T., Dalsky, G. P., Holloszy, J. O. (1992). Body composition of healthy sedentary and trained, young and older men and women. Medicine and Science in Sports Exercize, 24 (7), 832-837. Kyle, U. G., Melzer, K., Kayser, B., Picard-Kossovsky, Gremion, G., Pichard, C., (2006). Eight-Year Longitudinal Changes in Body Composition in Healthy Swiss Adults. Journal of the American College of Nutrition, 25 (6), 493-501. Mišigoj Durakovic, M. (2006). Kinantropology - biological aspects of physical exercise. Zagreb: Faculty of Kinesiology.